Analisis Pengaruh Waktu Etsa Terhadap Ukuran Struktur Mikrografi Material Logam dan Paduannya - Fitrianti Sugiono, Friska Ayu; Sugiono, Ratih Anggraeni; Munawwaroh, Dita (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2023)
In the world of the manufacturing industry, knowledge about the quality of the materials used is very important. This aims to guarantee the quality of the processing of primary materials into semi-finished and finished materials. One of the things that can be done to determine the quality of a metal is to know the micrographic structure of the metal and its contents in the metal. Another alternative that can be used to determine the amount of carbon in metal is photography which is useful for seeing large and small grains of steel. The research concrete iron, cast iron cast iron, amutite steel, and silver steel. The methods used in this study include grinding, polishing, etching, and microstructural observations using an optical microscope.